2004
DOI: 10.1083/jcb.200308158
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a hypercontraction-induced myopathy in Drosophila caused by mutations in Mhc

Abstract: The Myosin heavy chain (Mhc) locus encodes the muscle-specific motor mediating contraction in Drosophila. In a screen for temperature-sensitive behavioral mutants, we have identified two dominant Mhc alleles that lead to a hypercontraction-induced myopathy. These mutants are caused by single point mutations in the ATP binding/hydrolysis domain of Mhc and lead to degeneration of the flight muscles. Electrophysiological analysis in the adult giant fiber flight circuit demonstrates temperature-dependent seizure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…In addition to muscle hypercontraction and degeneration, Mhc mutants display abnormal TS behavior at restrictive temperatures, reflected in an acute loss of motor coordination and walking ability at 38°C. Most surprisingly, we found that TS-induced behavioral dysfunction was a common feature of all Drosophila hypercontraction muscle mutants assayed, in contrast to muscle mutants that lead to hypocontraction (5). These shared behavioral defects suggest that hypercontracted muscles have fundamentally different electrical properties than hypocontracted and normal muscles, resulting in TS dysfunction at elevated temperatures.…”
mentioning
confidence: 76%
See 3 more Smart Citations
“…In addition to muscle hypercontraction and degeneration, Mhc mutants display abnormal TS behavior at restrictive temperatures, reflected in an acute loss of motor coordination and walking ability at 38°C. Most surprisingly, we found that TS-induced behavioral dysfunction was a common feature of all Drosophila hypercontraction muscle mutants assayed, in contrast to muscle mutants that lead to hypocontraction (5). These shared behavioral defects suggest that hypercontracted muscles have fundamentally different electrical properties than hypocontracted and normal muscles, resulting in TS dysfunction at elevated temperatures.…”
mentioning
confidence: 76%
“…This downregulation may be responsible for potential Ca 2ϩ homeostasis defects in Mhc flight muscles. Indeed, our previous analysis suggested that intracellular Ca 2ϩ is dysregulated in Mhc mutant fibers, as larval body wall muscles exhibit spontaneous contraction cycles even in the absence of external Ca 2ϩ (5). A subset of the genes that were identified as differentially regulated in our hypercontraction-induced myopathy model have been implicated previously in activity-dependent synaptic plasticity in mammals.…”
Section: -L)mentioning
confidence: 99%
See 2 more Smart Citations
“…Drosophila age in weeks, and they share common mechanisms that determine aging rates and longevity with higher organisms (Parkes et al, 1999;Finch and Ruvkun, 2001;Tatar et al, 2003;Wessells and Bodmer, 2007). Thus, the fly is an extremely powerful model for studying the progression of myosin-related skeletal and cardiac muscle dysfunction.Two myosin point mutations in the Drosophila Mhc gene, D45 and Mhc 5 , were localized in proximity to coding regions for loops and linkers of the transducer (Kronert et al, 1999;Montana and Littleton, 2004). These mutations are in Mhc constitutive exons 5 and 4, respectively.…”
mentioning
confidence: 99%